Pengaruh Profitabilitas, Leverage, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Healthcare - Ainiyyah Mascida Eka Putri; Ani Hidayati (Journal of Trends Economics and Accounting Research, 2024)
This research aims to test and determine the influence of Profitability, Leverage and Company Size on Company Value in Healthcare Sector Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) in 2018 - 2022. Profitability is measured by Return On Assets (ROA), Leverage is measured by Debt to Equity (DER), Company Size is measured by Market Capitalization (MC) and Company Value is measured by Price to Book Value (PBV). This type of research is quantitative research. The population used in this research is healthcare sector manufacturing companies listed on the Indonesia Stock Exchange (BEI). The technique used was the Purposive Sampling technique and obtained 7 manufacturing companies in the healthcare sector to be used as samples. The analysis techniques used in this research are classical assumption analysis, multiple linear regression analysis and hypothesis testing which are processed using the SPSS version 25 program. In this research the results show that profitability and company size partially have a positive and significant effect on company value, while leverage partially has a negative and insignificant effect on company value and profitability, leverage and company size simultaneously or together have a significant effect on company value